A Plea for (In)Human-centred AI - Braun, Matthias; Meacham, Darian (Philosophy & Technology, 2024)
In this article, we use the account of the “inhuman” that is developed in the work of the French philosopher Jean-François Lyotard to develop a critique of human-centred AI. We argue that Lyotard’s philosophy not only provides resources for a negative critique of human-centred AI discourse, but also contains inspiration for a more constructive account of how the discourse around human-centred AI can take a broader view of the human that includes key dimensions of Lyotard’s inhuman, namely performativity, vulnerability, and novelty. We link these dimensions to questions of epistemic injustice and social recognition. In this way, we hope to develop a proposal for what a richer and more meaningful understanding of human-centred AI might look like.
Created from Fastlane, Scopus look-up
Keywords: Critical theory; Epistemic injustice; Ethics; Human-centred AI; Inhuman